A Narrative Study on Students’ Perception Towards Using TED Talks Videosfor Listening Comprehension - Rosanti, Zarina (Universitas Nusantara PGRI Kediri, 2025)
This narrative study aimed to explore undergraduate students’ perceptions of using TED Talks videos to enhance their comprehension skills and the challenges they faced in the process.The research employs a qualitative narrative inquiry approach to explore the experiences of second-semester English major students at Universitas Tanjungpura during the 2022/2023 academic year. Data were collected through written reflections using narrative frames and semi-structured interviews with three purposively selected participants who had experience with TED Talk videos in their listening comprehension courses. Thematic analysis was conducted to identify patterns and themes from the collected data.The respondents shared their experiences through written and oral narratives, highlighting the benefits, challenges, and strategies they employed when using TED Talks for listening comprehension. The findings revealed that students valued TED Talks for their role in expanding vocabulary, exposing learners to diverse topics, and providing motivational content. However, challenges such as fast speech, unfamiliar vocabulary, and audio quality issues were also identified. To overcome these obstacles, students employed strategies such as active listening, note-taking, and summarizing key concepts points.. In conclusion, this study provides valuable insights into students' experiences with TED Talk videos, emphasizing their potential benefits while acknowledging the challenges that need to be addressed in educational settings.